THE ROLE OF TEACHER IN USING TEXTBOOK - Hamdan - Anwari (Politeknik Negeri Bengkalis, 2021)
Abstract : This research is to give relevant information in teaching by using textbook in the classroom. Teacher uses the textbook as standardization in delivering the material. Textbook becomes the resource in teaching. there are some benefits why teacher uses textbook, there are the teacher needs standardization from the quality and quantity of the education, the teacher has to adapt the material which is available in the textbook, The teacher needs source to deliver the material to the students.This research method conducted by acquired literature study. In using the textbook the teacher should have some roles they are the roles of teacher are as a controller, organizer, assessor, prompter, resource, tutor, and observer. All the teacher roles above are to make adaption the material. The teacher should select the appropriate material, teacher should have strategy how the activity is done, teacher takes the material which is deeply needed by the students, teacher gives assessment to know how far the students understand in learning the material.